2020
DOI: 10.3892/ol.2020.11694
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of EHMT2 associated with H3K9me2 level contributes to the poor prognosis of gastric cancer

Abstract: Di-methylated lysine 9 of histone H3 (H3K9me2), regulated by histone methyltransferases, is involved in the epigenetic regulation of tumor-associated genes. The present study aimed to evaluate whether the H3K9me2 methylation level is associated with the expression level of euchromatic histone lysine methyltransferase 2 (EHMT2) in the prognosis of gastric cancer (GC). H3K9me2 methylation level and EHMT2 expression level were detected by immunohistochemistry in 118 GC samples. The clinicopathological significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…These epigenetic modifications, which result in altered chromatin structure and gene expression were reported in different types of cancers [ 108 ] ( Figure 3 ). G9a was overexpressed in breast, gastric, ovarian, cervical, endometrial, prostate, lung, colorectal, liver, urinary bladder, and brain cancers, as well as in hematological malignancies, melanoma, and cholangiocarcinoma, leading to aberrant H3K9 methylation [ 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. One of the main reasons for this increase in G9a expression and H3K9 methylation is hypoxia [ 103 ].…”
Section: G9a In Cancermentioning
confidence: 99%
“…These epigenetic modifications, which result in altered chromatin structure and gene expression were reported in different types of cancers [ 108 ] ( Figure 3 ). G9a was overexpressed in breast, gastric, ovarian, cervical, endometrial, prostate, lung, colorectal, liver, urinary bladder, and brain cancers, as well as in hematological malignancies, melanoma, and cholangiocarcinoma, leading to aberrant H3K9 methylation [ 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ]. One of the main reasons for this increase in G9a expression and H3K9 methylation is hypoxia [ 103 ].…”
Section: G9a In Cancermentioning
confidence: 99%
“…Analysis of TCGA data showed that a number of histone modifiers are differentially expressed between GC and noncancer samples 28 . A more recent analysis of TCGA data focusing on HMTs found that the increased expression of G9a/ EHMT2, an H3K9 methyltransferase, is associated with poor prognosis, while its oncogenic effect may be mediated by activating the expression of MTOR via increasing promoter H3K9me1 [29][30][31] .…”
Section: Histone Modification and The Chromatin Landscape In Gastric ...mentioning
confidence: 99%
“…Immunohistochemistry data of paired lung adenocarcinoma and lung squamous cell carcinoma samples revealed a significant higher expression of G9a correlating with metastasis and a poor prognosis of patients[ 166 ]. In comparison, low expressions of H3K9me2 and G9a could predict a better prognosis for patients with gastric cancer[ 167 ].…”
Section: Histone Remodeling and Modification Regulating Autophagymentioning
confidence: 99%